Relationship between endotoxaemia and protein concentration of ascites in cirrhotic patients. Issue 3 (March 1979) - Tarao, K; Moroi, T; Nagakura, Y; Ikeuchi, T; Suyama, T; Endo, O; Fukushima, K
Abstract : Endotoxaemia was investigated by the Limulus assay in 42 cirrhotic patients with ascites and in 33 without ascites. The incidence of endotoxaemia in the former group (59.5%) was significantly (P less than 0.05) higher than in the latter (36.4%). Correlation between endotoxaemia and specific gravity and concentrations of total protein, albumin, and globulin in ascitic fluid was studied in the group with ascites. The specific gravity of ascites in 25 patients with endotoxaemia was significantly greater than that in 17 patients without endotoxaemia (P less than 0.01). The concentration of total protein in patients with endotoxaemia (13.95 +/- 7.18 milligram, mean +/- SD) was nearly twice as high (P less than 0.01) as in patients without endotoxaemia (7.49 +/- 3.60 milligram). The protein content of those who showed reactions greater or equal to 2(+) in the Limulus assay (16.78 +/- 7.14 milligram) was a significantly (P less than 0.05) higher than in those with 1(+) reaction (11.26 +/- 6.33 milligram). Moreover, the concentration of albumin in patients with endotoxaemia (7.68 +/- 4.60 milligram) was more than twice that of the patients without endotoxaemia (3.39 +/- 1.58 milligram, P less than 0.01). On the other hand, globulin concentration in patients with endotoxaemia was 1.6 times that of patients without endotoxaemia (P less than 0.01). Similar differences were noted between endotoxaemic and non-endotoxaemic patients in the ascites-to-serum ratio in protein, albumin, and globulin. These results suggest that in liver cirrhosis endotoxaemia may cause an increase in protein concentrations in ascitic fluid, and that it may be a precipitating factor in the formation of ascites.